Дискурсивно-концептуальні особливості категорії саморепрезентації (на матеріалі англомовного інтерв’ю) - Киричук, Лариса Миколаївна; Kyrychuk, L. M. (Волин. нац. ун-т ім. Лесі Українки, 2010)
Стаття присвячена вивченню дискурсивних особливостей позитивної саморепрезентації мовця, які, у свою чергу, визначають її концептуальну структуру. Концептуальні риси саморепрезентації аналізуються у межах прототипного підходу шляхом категоріального структурування; визначається ядро моделі саморепрезентації, зона навколо ядра та периферія. The paper is devoted to the study of discursive peculiarities of the speaker’s positive self-representation, which, in their turn, determine the conceptual structure of the latter. The conceptual features of self-representation are analyzed in the framework of prototype approach by means of categorical structuring; the nucleus of the model, its round the nucleus zone and its periphery are indicated.
Discoursive Conceptual Specificity of the Category of Self-Representation (on the material of English Interview)
Keywords: дискурс; discourse; стратегія; strategy; мовна особистість; speech personality; концепт; concept; категория саморепрезентации; category of self-representation